Preparation method of powder coating with super corrosion resistance

By using the cross-linking reaction of modified aldehyde ketone resin and bisphenol A type epoxy resin in powder coatings, and adding anti-corrosion masterbatches to form a protective oxide film, the problems of poor corrosion resistance and high cost of existing powder coatings are solved, and the preparation of highly efficient and economical ultra-preservative powder coatings is achieved.

CN119799127APending Publication Date: 2025-04-11CHUZHOU DONGTU CHEMICAL NEW MATERIALS TECHNOLOGY CO LTD

Patent Information

Application Number
CN202510001645.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-02
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The corrosion resistance of existing epoxy resin powder coatings is relatively average, especially because the high cost of zinc powder leads to the high formulation cost of zinc-rich powder coatings. It is urgent to develop a method for preparing ultra-preservative powder coatings.

Method used

Modified aldehyde ketone resin, bisphenol A type epoxy resin, anticorrosion masterbatch (composed of bisphenol A type epoxy resin, zinc powder, iron phosphorus powder, alumina and graphene), as well as curing agents and leveling agents, and super anticorrosion powder coatings are prepared through cross-linking reactions and forming protective oxide films.

Benefits of technology

It significantly improves the anticorrosion and adhesion of powder coatings, can effectively resist the corrosion of corrosive substances such as acids, alkalis and salts, and at the same time reduces the amount of zinc powder added and reduces the cost of formula.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of coatings, in particular to a preparation method of a powder coating with super corrosion resistance, which is prepared from the following raw materials in parts by mass: 15-20 parts of modified aldehyde ketone resin, 60-68 parts of bisphenol A epoxy resin, 15-20 parts of corrosion-resistant master batch, 5-8 parts of curing agent and 1.5-2.2 parts of flatting agent. The anti-corrosion master batch is prepared from bisphenol A epoxy resin, zinc powder, ferrophosphorus powder, aluminum oxide and graphene; wherein the modified aldehyde ketone resin can generate a cross-linking reaction with active functional groups of the bisphenol A epoxy resin, so that the adhesive force of the coating is enhanced, a corrosive medium can be prevented from permeating to the surface of a base material, and a formed cross-linked network structure enables the coating to be more compact and pores to be reduced, so that the resistance to corrosive substances such as acid, alkali and salt is improved; due to the addition of the anti-corrosion master batch, the powder coating with an excellent anti-corrosion effect can be obtained on the premise that the addition amount of the zinc powder is obviously reduced, and the powder coating has a wide application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of coatings, and in particular to a method for preparing a powder coating with super anti-corrosion performance. Background Art

[0002] Powder coating is completely different from general coating. It exists in the form of fine powder. Because it does not use solvents, it is called powder coating. The main characteristics of powder coating are: harmless, high efficiency, resource saving and environmental protection. Powder coating is a new type of solvent-free, 100% solid powder coating. It has the characteristics of no solvent, no pollution, energy and resource saving, reduced labor intensity and high mechanical strength of coating film. Powder coating is a solid powder synthetic resin coating composed of solid resin, pigment, filler and additives.

[0003] Since epoxy resin powder coating has excellent metal adhesion, hardness, flexibility and good impact strength, it is widely used. However, the corrosion resistance of existing epoxy resin powder coating is relatively general, which limits its application. For example, patent technology document CN118064034B discloses a wear-resistant epoxy resin powder coating and a preparation method thereof, comprising the following raw materials in parts by weight: 35-50 parts of bisphenol A diglycidyl ether, 15-25 parts of o-cresol polyglycidyl ether, 3-6 parts of curing agent, 1.2-1.6 parts of leveling agent, 0.2-0.4 parts of accelerator, 1-1.4 parts of flexibilizer, 5-10 parts of polydopamine coated nanofiller. Among them, the polydopamine coated nanofiller is prepared by coating and modifying the surface of the nanofiller with dopamine, thereby improving the dispersibility and compatibility of the nanofiller in the epoxy resin, so that the nanofiller can give full play to the reinforcing and hardening effect, which is conducive to improving the wear resistance and surface hardness of the coating, but the corrosion resistance of the prepared powder coating is relatively general.

[0004] In order to achieve excellent corrosion resistance, existing powder coatings usually choose to add a large amount of zinc powder in the formula. This product is usually called zinc-rich powder coating. For example, patent technical document CN114213937A proposes a zinc-rich powder coating and its preparation method and application, including the following preparation raw materials: 20-50 parts of epoxy resin, 0.5-2.0 parts of curing agent, 0.05-0.5 parts of catalyst, 60-75 parts of zinc powder, 0.05-0.1 parts of conductive powder, 0.4-1.2 parts of leveling agent, 0.1-0.5 parts of degassing agent, and 0.1-0.5 parts of charge enhancer; the zinc powder addition amount reaches more than 60wt%. Due to the high price of zinc powder, this directly leads to the excessively high formula cost of the powder coating.

[0005] Therefore, according to the above-mentioned related technologies, it is urgent to develop a method for preparing a powder coating with super anti-corrosion performance. Summary of the invention

[0006] In view of this, the purpose of the present invention is to provide a method for preparing a powder coating with super anti-corrosion performance to solve the problem of poor anti-corrosion performance of powder coatings in the prior art.

[0007] Based on the above purpose, the present invention provides a method for preparing a powder coating with super anti-corrosion performance.

[0008] A method for preparing a powder coating with super anti-corrosion performance, which is prepared from the following raw materials in parts by weight: 15-20 parts of modified aldehyde-ketone resin, 60-68 parts of bisphenol A epoxy resin, 15-20 parts of anti-corrosion masterbatch, 5-8 parts of curing agent, and 1.5-2.2 parts of leveling agent;

[0009] The anticorrosive masterbatch is prepared from bisphenol A epoxy resin, zinc powder, ferrophosphorus powder, aluminum oxide and graphene.

[0010] Preferably, the preparation method of the modified aldehyde-ketone resin is as follows:

[0011] Step A1. Add cyclohexanone to a formaldehyde aqueous solution, add a sodium hydroxide solution, heat to 75-85 ° C and react for 3-5 hours to obtain a pre-treated solution;

[0012] Step A2. Add melamine and cyclohexanone to the pretreatment liquid at 75-85°C, add sodium hydroxide to adjust the pH to 10-11, heat to 95-105°C, condense and reflux for 1-3h, add monohydrated citric acid to neutral pH, heat to 120-130°C and react for 5-8h, add 2,6-di-tert-butyl-4-methylphenol, mix, and obtain modified aldehyde-ketone resin.

[0013] Preferably, the mass ratio of cyclohexanone, formaldehyde aqueous solution and sodium hydroxide solution in step A1 is 48-52:120-140:2-5.

[0014] Preferably, the mass fraction of the formaldehyde aqueous solution in step A1 is 35%-40%;

[0015] The mass fraction of the sodium hydroxide solution in step A1 is 30%-35%.

[0016] Preferably, the mass ratio of the pretreatment liquid, melamine, cyclohexanone and 2,6-di-tert-butyl-4-methylphenol in step A2 is 160-180:6-8:48-52:8-12.

[0017] Preferably, the preparation method of the anticorrosive masterbatch is as follows:

[0018] Put bisphenol A epoxy resin, zinc powder, ferrophosphorus powder, alumina and graphene into a heating and mixing device, heat to 95-105°C, react for 5-8 hours, then cool, crush and sieve to obtain an anticorrosive masterbatch.

[0019] Preferably, the mass ratio of the bisphenol A epoxy resin, zinc powder, ferrophosphorus powder, aluminum oxide and graphene is 35-40:10-15:5-10:10-15:2-8.

[0020] Preferably, the particle size of the zinc powder is 600-800 mesh, the particle size of the ferrophosphorus powder is 600-800 mesh, the particle size of the aluminum oxide is 600-800 mesh, and the particle size of the graphene is 1200-1500 mesh.

[0021] Preferably, the curing agent is tetraethylenepentamine;

[0022] The leveling agent is polydimethylsiloxane.

[0023] Preferably, the preparation method of the super anti-corrosion powder coating is as follows:

[0024] The modified aldehyde-ketone resin, bisphenol A epoxy resin, anticorrosive masterbatch, curing agent and leveling agent are mixed and added into a high-speed mixer. After stirring at 2000-2200 r / min for 1-3 hours, the mixture is added into a twin-screw extruder for melt extrusion, slicing, crushing and passing through a 600-800 mesh sieve to obtain a powder coating with super anticorrosive performance.

[0025] Beneficial effects of the present invention:

[0026] The present invention provides a method for preparing a powder coating with super anti-corrosion performance. The present invention prepares the powder coating by adding modified aldehyde-ketone resin, bisphenol A epoxy resin, anti-corrosion masterbatch, curing agent and leveling agent, wherein the bisphenol A epoxy resin is used as a base resin, and the modified aldehyde-ketone resin can produce a cross-linking reaction with the active functional groups of the bisphenol A epoxy resin. The cross-linking reaction increases the bonding force between the resin and the substrate, enhances the adhesion of the coating, and can prevent the corrosive medium from penetrating into the surface of the substrate. The formed cross-linked network structure makes the coating denser and reduces the pores, thereby improving the resistance to corrosive substances such as acids, alkalis and salts.

[0027] The anti-corrosion masterbatch composed of bisphenol A epoxy resin, zinc powder, ferrophosphorus powder, alumina and graphene, when added to the epoxy resin curing system, the ferrophosphorus powder can form a protective oxide film to slow down the corrosion rate of the metal, the alumina can increase its density and reduce the penetration of corrosive media, and the high conductivity of graphene combined with zinc powder can form a more effective electrochemical protective layer. Under the premise of significantly reducing the amount of zinc powder added, a powder coating with excellent anti-corrosion effect can be obtained, which has broad application prospects. DETAILED DESCRIPTION

[0028] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments.

[0029] The sources and properties of some of the raw materials used in the present invention are as follows:

[0030] Bisphenol A epoxy resin was purchased from Hubei Shishun Biotechnology Co., Ltd.; ferrophosphorus powder was purchased from Jinan Dehou Chemical Co., Ltd.; cyclohexanone was purchased from Fuchen (Tianjin) Chemical Reagent Co., Ltd.; 2,6-di-tert-butyl-4-methylphenol was purchased from Juye Runjia Chemical Co., Ltd.; citric acid monohydrate was purchased from Shanghai Yuanye Biotechnology Co., Ltd.; the curing agent was tetraethylenepentamine, purchased from Jinan Aochen Chemical Co., Ltd.; the leveling agent was polydimethylsiloxane, purchased from Shanghai Yuanye Biotechnology Co., Ltd.

[0031] Embodiment 1: A method for preparing a powder coating with super anti-corrosion performance, comprising the following preparation method:

[0032] S1. Take 48g of cyclohexanone and add 120g of 35% aqueous formaldehyde solution, add 2g of 30% sodium hydroxide solution by mass, heat to 75 ° C and react for 3h to obtain a pre-treated solution;

[0033] S2. 160 g of the pre-treated liquid was added with 6 g of melamine and 48 g of cyclohexanone at 75 ° C, sodium hydroxide was added to adjust the pH value to 10, the temperature was raised to 95 ° C, condensed and refluxed for 1 h, citric acid monohydrate was added to a neutral pH, the temperature was raised to 120 ° C for 5-8 h, 8 g of 2,6-di-tert-butyl-4-methylphenol was added, and mixed to obtain a modified aldehyde-ketone resin;

[0034] S3. 35 g of bisphenol A epoxy resin, 10 g of zinc powder, 5 g of ferrophosphorus powder, 10 g of alumina and 2 g of graphene were placed in a heating and mixing device, heated to 95 ° C for 5 h, then cooled, crushed and sieved to obtain an anticorrosive masterbatch, wherein the particle size of the zinc powder is 600 mesh, the particle size of the ferrophosphorus powder is 600 mesh, the particle size of the alumina is 600 mesh, and the particle size of the graphene is 1200 mesh;

[0035] S4. Mix 15g of modified aldehyde-ketone resin, 60g of bisphenol A epoxy resin, 15g of anti-corrosion masterbatch, 5g of tetraethylenepentamine and 1.5g of polydimethylsiloxane, add them to a high-speed mixer, stir at 2000r / min for 1h, add them to a twin-screw extruder for melt extrusion, slice, crush and pass through a 600-mesh sieve to obtain a powder coating with super anti-corrosion performance.

[0036] Embodiment 2: A method for preparing a powder coating with super anti-corrosion performance, comprising the following preparation method:

[0037] S1. Take 49g of cyclohexanone and add 128g of 36% aqueous formaldehyde solution, add 3g of 31% sodium hydroxide solution by mass, heat to 78 ° C and react for 3.5h to obtain a pre-treated solution;

[0038] S2. 165 g of the pre-treated liquid was added with 6.5 g of melamine and 49 g of cyclohexanone at 78 ° C, sodium hydroxide was added to adjust the pH value to 10, the temperature was raised to 98 ° C, condensed and refluxed for 1.5 h, citric acid monohydrate was added to a neutral pH, the temperature was raised to 122 ° C for 6 h, 9 g of 2,6-di-tert-butyl-4-methylphenol was added, and mixed to obtain a modified aldehyde-ketone resin;

[0039] S3. 36 g of bisphenol A epoxy resin, 11 g of zinc powder, 6 g of ferrophosphorus powder, 11 g of alumina and 4 g of graphene were placed in a heating and mixing device, heated to 98 ° C for 6 h, then cooled, crushed and sieved to obtain an anticorrosive masterbatch, wherein the particle size of the zinc powder is 650 mesh, the particle size of the ferrophosphorus powder is 650 mesh, the particle size of the alumina is 650 mesh, and the particle size of the graphene is 1250 mesh;

[0040] S4. Mix 16g of modified aldehyde-ketone resin, 62g of bisphenol A epoxy resin, 16g of anticorrosive masterbatch, 5.5g of tetraethylenepentamine and 1.6g of polydimethylsiloxane, add them to a high-speed mixer, stir at 2050r / min for 1.5h, add them to a twin-screw extruder for melt extrusion, slice, crush and pass through a 650-mesh sieve to obtain a powder coating with super anti-corrosion performance.

[0041] Embodiment 3: A method for preparing a powder coating with super anti-corrosion performance, comprising the following preparation method:

[0042] S1. Take 50g of cyclohexanone and add 130g of 37% formaldehyde aqueous solution, add 3.5g of 32% sodium hydroxide solution by mass, heat to 80 ° C and react for 4h to obtain a pre-treated solution;

[0043] S2. 170 g of the pre-treated liquid was added with 7 g of melamine and 50 g of cyclohexanone at 80 ° C, sodium hydroxide was added to adjust the pH value to 10, the temperature was raised to 100 ° C, condensed and refluxed for 2 h, citric acid monohydrate was added to a neutral pH, the temperature was raised to 124 ° C and reacted for 6.5 h, 10 g of 2,6-di-tert-butyl-4-methylphenol was added, and mixed to obtain a modified aldehyde-ketone resin;

[0044] S3. 37 g of bisphenol A epoxy resin, 12 g of zinc powder, 7 g of ferrophosphorus powder, 12 g of alumina and 5 g of graphene were placed in a heating and mixing device, heated to 100 ° C and reacted for 6.5 h, then cooled, crushed and sieved to obtain an anticorrosive masterbatch, wherein the particle size of the zinc powder is 700 mesh, the particle size of the ferrophosphorus powder is 700 mesh, the particle size of the alumina is 700 mesh, and the particle size of the graphene is 1300 mesh;

[0045] S4. Mix 17g of modified aldehyde-ketone resin, 63g of bisphenol A epoxy resin, 17g of anticorrosive masterbatch, 6g of tetraethylenepentamine and 1.8g of polydimethylsiloxane, add them to a high-speed mixer, stir at 2100r / min for 2h, add them to a twin-screw extruder for melt extrusion, slice, crush and pass through a 700-mesh sieve to obtain a powder coating with super anti-corrosion performance.

[0046] Example 4: A method for preparing a powder coating with super anti-corrosion performance, comprising the following preparation method:

[0047] S1. Take 51g of cyclohexanone and add 134g of 38% aqueous formaldehyde solution, add 4g of 33% sodium hydroxide solution by mass, heat to 82 ° C and react for 4.4h to obtain a pre-treated solution;

[0048] S2. 7.4 g of melamine and 51 g of cyclohexanone were added to 174 g of the pre-treated liquid at 82 ° C, sodium hydroxide was added to adjust the pH to 11, the temperature was raised to 102 ° C, condensed and refluxed for 2.4 h, citric acid monohydrate was added to a neutral pH, the temperature was raised to 126 ° C for 7 h, 11 g of 2,6-di-tert-butyl-4-methylphenol was added, and mixed to obtain a modified aldehyde-ketone resin;

[0049] S3. 38 g of bisphenol A epoxy resin, 13 g of zinc powder, 8 g of ferrophosphorus powder, 13 g of alumina and 6 g of graphene were placed in a heating and mixing device, heated to 102 ° C, reacted for 7 h, cooled, crushed and sieved to obtain an anticorrosive masterbatch, wherein the particle size of the zinc powder is 740 mesh, the particle size of the ferrophosphorus powder is 740 mesh, the particle size of the alumina is 740 mesh, and the particle size of the graphene is 1400 mesh;

[0050] S4. Mix 18g of modified aldehyde-ketone resin, 65g of bisphenol A epoxy resin, 18g of anticorrosive masterbatch, 7g of tetraethylenepentamine and 2g of polydimethylsiloxane, add them to a high-speed mixer, stir at 2140r / min for 2.4h, add them to a twin-screw extruder for melt extrusion, slice, crush and pass through a 740-mesh sieve to obtain a powder coating with super anticorrosive performance.

[0051] Embodiment 5: A method for preparing a powder coating with super anti-corrosion performance, comprising the following preparation method:

[0052] S1. Take 51.5g of cyclohexanone and add 138g of 39% aqueous formaldehyde solution, add 4.5g of 34% sodium hydroxide solution by mass, heat to 84 ° C and react for 4.8h to obtain a pre-treated solution;

[0053] S2. 7.8 g of melamine and 51.5 g of cyclohexanone were added to 178 g of the pre-treated liquid at 84 ° C, sodium hydroxide was added to adjust the pH to 11, the temperature was raised to 104 ° C, condensed and refluxed for 2.8 h, citric acid monohydrate was added to a neutral pH, the temperature was raised to 128 ° C and reacted for 7.5 h, 11.5 g of 2,6-di-tert-butyl-4-methylphenol was added, and mixed to obtain a modified aldehyde-ketone resin;

[0054] S3. 39 g of bisphenol A epoxy resin, 14 g of zinc powder, 9 g of ferrophosphorus powder, 14 g of alumina and 7 g of graphene were placed in a heating and mixing device, heated to 104 ° C for 7.5 h, then cooled, crushed and sieved to obtain an anticorrosive masterbatch, wherein the particle size of the zinc powder is 780 mesh, the particle size of the ferrophosphorus powder is 780 mesh, the particle size of the alumina is 780 mesh, and the particle size of the graphene is 1450 mesh;

[0055] S4. Mix 19g of modified aldehyde-ketone resin, 66g of bisphenol A epoxy resin, 19g of anticorrosive masterbatch, 7.5g of tetraethylenepentamine and 2.1g of polydimethylsiloxane, add them to a high-speed mixer, stir at 2180r / min for 2.8h, add them to a twin-screw extruder for melt extrusion, slice, crush and pass through a 780-mesh sieve to obtain a powder coating with super anti-corrosion performance.

[0056] Example 6: A method for preparing a powder coating with super anti-corrosion performance, comprising the following preparation method:

[0057] S1. Take 52g of cyclohexanone and add 140g of 40% formaldehyde aqueous solution, add 5g of 35% sodium hydroxide solution by mass, heat to 85 ° C and react for 5h to obtain a pre-treated solution;

[0058] S2. 8 g of melamine and 52 g of cyclohexanone were added to 180 g of the pre-treated liquid at 85 ° C, sodium hydroxide was added to adjust the pH to 11, the temperature was raised to 105 ° C, condensed and refluxed for 3 h, citric acid monohydrate was added to a neutral pH, the temperature was raised to 130 ° C for 8 h, 12 g of 2,6-di-tert-butyl-4-methylphenol was added, and mixed to obtain a modified aldehyde-ketone resin;

[0059] S3. 40g of bisphenol A epoxy resin, 15g of zinc powder, 10g of ferrophosphorus powder, 15g of alumina and 8g of graphene were placed in a heating and mixing device, heated to 105°C for 8h, cooled, crushed and sieved to obtain an anticorrosive masterbatch, wherein the particle size of the zinc powder is 800 mesh, the particle size of the ferrophosphorus powder is 800 mesh, the particle size of the alumina is 800 mesh, and the particle size of the graphene is 1500 mesh;

[0060] S4. Mix 20g of modified aldehyde-ketone resin, 68g of bisphenol A epoxy resin, 20g of anticorrosive masterbatch, 8g of tetraethylenepentamine and 2.2g of polydimethylsiloxane, add them to a high-speed mixer, stir at 2200r / min for 3h, add them to a twin-screw extruder for melt extrusion, slice, crush and pass through an 800-mesh sieve to obtain a powder coating with super anti-corrosion performance.

[0061] Comparative Example 1:

[0062] Compared with Example 1, this comparative example does not add modified aldehyde-ketone resin during the preparation process of the super anti-corrosion powder coating, and the remaining steps and parameters are the same, which will not be repeated in this comparative example. Finally, a super anti-corrosion powder coating is obtained.

[0063] Comparative Example 2:

[0064] Compared with Example 1, this comparative example only replaces the "modified aldehyde-ketone resin" with "melamine formaldehyde resin", and the remaining steps and parameters are the same, which will not be repeated in this comparative example, and finally a powder coating with super anti-corrosion performance is obtained.

[0065] Comparative Example 3:

[0066] Compared with Example 1, this comparative example only replaces "15g modified aldehyde-ketone resin, 60g bisphenol A epoxy resin" with "60g modified aldehyde-ketone resin, 15g bisphenol A epoxy resin", and the remaining steps and parameters are the same. This comparative example will not be repeated, and finally a powder coating with super anti-corrosion performance is obtained.

[0067] Comparative Example 4:

[0068] Compared with Example 1, this comparative example does not add anticorrosive masterbatch during the preparation of the super anticorrosive powder coating, and the remaining steps and parameters are the same, which will not be repeated in this comparative example. Finally, a super anticorrosive powder coating is obtained.

[0069] Comparative Example 5:

[0070] Compared with Example 1, this comparative example only replaces the "anticorrosion masterbatch" with "zinc powder", and the remaining steps and parameters are the same, which will not be repeated in this comparative example. Finally, a powder coating with super anticorrosion performance is obtained.

[0071] Performance Test:

[0072] Anti-corrosion performance test:

[0073] The salt spray resistance test was carried out with reference to the test standard GB / T1771-2007 "Determination of neutral salt spray resistance of paints and varnishes". A 70mm×150mm×3mm Q235 steel plate was used as the substrate, and the ultra-corrosion resistant powder coatings prepared in Examples 1 to 6 and Comparative Examples 1 to 5 were added with water and sprayed on the substrate. The spraying thickness was about 200μm. After the coating was completely cured, it was placed in a salt spray test box to test the single-sided corrosion width of the neutral salt spray 500 coating.

[0074] Adhesion test:

[0075] Adhesion test was carried out according to GB / T1720-79 "Paint film adhesion test method" test standard. 25g of the super anti-corrosion powder coating prepared in Example 1 to Example 6 and Comparative Example 1 to Comparative Example 5 was added with 10mL of water and mixed and evenly coated on the surface of 50mm×100m×0.3mm tinplate sheet. After the coating was completely cured and reached the curing age, it was measured using a paint film adhesion tester. The integrity of the paint film within the range of the rolling line scratch was analyzed to evaluate the coating film adhesion.

[0076] Alkali resistance test:

[0077] The alkali resistance test was carried out according to the test standard of GB / T9265-2009 "Determination of Alkali Resistance of Architectural Coatings". Three 150 mm × 100 mm × 5 mm asbestos-free fiber cement boards were selected according to JC / T412.1-2006 and the surfaces were cleaned and dried according to GB / T9271. The ultra-corrosion-resistant powder coatings prepared in Examples 1 to 6 and Comparative Examples 1 to 5 were evenly coated on the surfaces of the test boards using a 120 μm wire rod coater. The powder coatings were heated at a temperature of (23 °C) according to GB / T9265-2009. ±2)℃, and maintain according to the time specified in the national standard. After drying, the dry film thickness is measured to be 80μm. The sample needs to be sealed before the water resistance test. The test immersion liquid needs to be a calcium hydroxide supernatant that meets the requirements of GB / T9265-2009 (prepare an excess of calcium hydroxide alkaline solution, stir it thoroughly, and take the supernatant as the test solution after standing for 24 hours). Put three test panels in it, and soak 2 / 3 of the test panels in water for 60d. After the immersion, rinse with water, dry with filter paper, and observe whether the coating has cracks, bubbles, peeling, etc.

[0078] Table 1 Summary of experimental data in Examples 1 to 6 and Comparative Examples 1 to 5

[0079] project Salt spray resistance / 500h Adhesion Alkali resistance Example 1 Unilateral corrosion <2mm Scratches are relatively complete No cracks, no blistering, no peeling Example 2 Unilateral corrosion <2mm Scratches are relatively complete No cracks, no blistering, no peeling Example 3 Unilateral corrosion <2mm Scratches are relatively complete No cracks, no blistering, no peeling Example 4 Unilateral corrosion <2mm Scratches are relatively complete No cracks, no blistering, no peeling Example 5 Unilateral corrosion <2mm Scratches are relatively complete No cracks, no blistering, no peeling Example 6 Unilateral corrosion <2mm Scratches are relatively complete No cracks, no blistering, no peeling Comparative Example 1 Unilateral corrosion <8mm Scratches and severe damage Cracks, blistering, peeling Comparative Example 2 Unilateral corrosion <7mm Scratch damage Cracks, bubbles Comparative Example 3 Unilateral corrosion <10mm Scratch damage Cracks, bubbles Comparative Example 4 Unilateral corrosion <12mm Scratches and severe damage Cracks, blistering, peeling Comparative Example 5 Unilateral corrosion <6mm Scratch damage Cracks, bubbles

[0080] Data Analysis:

[0081] As can be seen from Table 1, the super anti-corrosion powder coating prepared by the present invention has better anti-corrosion performance and adhesion, and can improve resistance to corrosive substances such as alkali and salt;

[0082] This may be because the powder coating is made by adding modified aldehyde-ketone resin, bisphenol A epoxy resin, anti-corrosion masterbatch, curing agent, and leveling agent, in which bisphenol A epoxy resin is used as the base resin. The modified aldehyde-ketone resin can produce a cross-linking reaction with the active functional groups of the bisphenol A epoxy resin. The cross-linking reaction increases the bonding force between the resin and the substrate, enhances the adhesion of the coating, and can prevent the corrosive medium from penetrating into the surface of the substrate. The formed cross-linked network structure makes the coating denser and reduces the porosity, thereby improving the resistance to corrosive substances such as acids, alkalis, and salts. Without the modified aldehyde-ketone resin, the cross-linking degree of the bisphenol A epoxy resin in the powder coating decreases, the adhesion of the coating decreases, and the coating is relatively loose. The anticorrosive medium is more likely to corrode the substrate through the coating. When the modified aldehyde-ketone resin is replaced by melamine formaldehyde resin, it can be seen from Table 1 that the anticorrosive performance of the coating is reduced. This may be because the polar groups such as ketone and hydroxyl groups in the modified aldehyde-ketone resin can enhance the chemical bonding with the substrate, improve the adhesion of the coating film, and be more resistant to corrosion by the corrosive medium. When the amount of modified aldehyde-ketone resin and bisphenol A epoxy resin is replaced, it can be seen from Table 1 that the anticorrosive performance of the coating is reduced. This may be because bisphenol A epoxy resin has a higher cross-linking density and excellent chemical stability, while the cross-linking density of the modified aldehyde-ketone resin may not be as high as that of bisphenol A epoxy resin, and the formed coating may not be dense enough, resulting in a weakened anticorrosive effect.

[0083] The anti-corrosion masterbatch composed of bisphenol A epoxy resin, zinc powder, ferrophosphorus powder, alumina and graphene, when added to the epoxy resin curing system, the ferrophosphorus powder can form a protective oxide film to slow down the corrosion rate of the metal, the alumina can increase its density and reduce the penetration of corrosive media, and the high conductivity of graphene combined with zinc powder can form a more effective electrochemical protective layer. Under the premise of significantly reducing the amount of zinc powder added, a powder coating with excellent anti-corrosion effect can be obtained.

[0084] Those skilled in the art should understand that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of the present invention is limited to these examples. Under the concept of the present invention, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of the different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity.

[0085] The present invention is intended to cover all such substitutions, modifications and variations that fall within the broad scope of the appended claims. Therefore, any omissions, modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A method for preparing a powder coating with super anti-corrosion performance, characterized in that: The method is prepared from the following raw materials in parts by weight: 15-20 parts of modified aldehyde-ketone resin, 60-68 parts of bisphenol A epoxy resin, 15-20 parts of anticorrosive masterbatch, 5-8 parts of curing agent and 1.5-2.2 parts of leveling agent; The anticorrosive masterbatch is prepared from bisphenol A epoxy resin, zinc powder, ferrophosphorus powder, aluminum oxide and graphene.

2. The method for preparing the super anti-corrosion powder coating according to claim 1, characterized in that: The preparation method of the modified aldehyde-ketone resin is as follows: Step A1. Add cyclohexanone to a formaldehyde aqueous solution, add a sodium hydroxide solution, heat to 75-85 ° C and react for 3-5 hours to obtain a pre-treated solution; Step A2. Add melamine and cyclohexanone to the pretreatment liquid at 75-85°C, add sodium hydroxide to adjust the pH to 10-11, heat to 95-105°C, condense and reflux for 1-3h, add monohydrated citric acid to neutral pH, heat to 120-130°C and react for 5-8h, add 2,6-di-tert-butyl-4-methylphenol, mix, and obtain modified aldehyde-ketone resin.

3. The method for preparing the super anti-corrosion powder coating according to claim 2, characterized in that: The mass ratio of cyclohexanone, formaldehyde aqueous solution and sodium hydroxide solution in step A1 is 48-52:120-140:2-5.

4. The method for preparing the super anti-corrosion powder coating according to claim 2, characterized in that: The mass fraction of the formaldehyde aqueous solution in step A1 is 35%-40%; The mass fraction of the sodium hydroxide solution in step A1 is 30%-35%.

5. The method for preparing the super anti-corrosion powder coating according to claim 2, characterized in that: The mass ratio of the pretreatment liquid, melamine, cyclohexanone and 2,6-di-tert-butyl-4-methylphenol in step A2 is 160-180:6-8:48-52:8-12.

6. The method for preparing the super anti-corrosion powder coating according to claim 1, characterized in that: The preparation method of anticorrosive masterbatch is as follows: Put bisphenol A epoxy resin, zinc powder, ferrophosphorus powder, alumina and graphene into a heating and mixing device, heat to 95-105°C, react for 5-8 hours, then cool, crush and sieve to obtain an anticorrosive masterbatch.

7. The method for preparing the ultra-corrosion resistant powder coating according to claim 6, characterized in that: The mass ratio of the bisphenol A epoxy resin, zinc powder, ferrophosphorus powder, aluminum oxide and graphene is 35-40:10-15:5-10:10-15:2-8.

8. The method for preparing the ultra-corrosion resistant powder coating according to claim 6, characterized in that: The particle size of the zinc powder is 600-800 mesh, the particle size of the ferrophosphorus powder is 600-800 mesh, the particle size of the aluminum oxide is 600-800 mesh, and the particle size of the graphene is 1200-1500 mesh.

9. The method for preparing the ultra-corrosion resistant powder coating according to claim 1, characterized in that: The curing agent is tetraethylenepentamine; The leveling agent is polydimethylsiloxane.

10. The method for preparing the super anti-corrosion powder coating according to claim 1, characterized in that: The preparation method of the super anti-corrosion powder coating is as follows: The modified aldehyde-ketone resin, bisphenol A epoxy resin, anticorrosive masterbatch, curing agent and leveling agent are mixed and added into a high-speed mixer. After stirring at 2000-2200 r / min for 1-3 hours, the mixture is added into a twin-screw extruder for melt extrusion, slicing, crushing and passing through a 600-800 mesh sieve to obtain a powder coating with super anticorrosive performance.

Citation Information

Patent Citations

  • Zinc-rich powder coating as well as preparation method and application thereof

    CN114213937A

  • A kind of wear-resistant epoxy resin powder coating and preparation method thereof

    CN118064034B

Cited By

  • Aldehyde ketone solid standard substance and preparation method thereof

    CN120522307A